PENGELOLA KEUANGAN DALAM REALITAS â€œSISI GELAPâ€ - Kuswantoro, Rinto; Firman, Akhmad; Abdullah, Muntu (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
The purpose of this study is to find out why financial managers still want to be involved in the dark side that becomes the reality in their profession. The research method used in this study is Transsendental Phenomenology, this method is believed to be able to reveal the deepest side of the informant. The way to do this is to delay the justification (ephoce) of the outer consciousness, then the outermost consciousness is developed to get the deepest awareness.The results of this study found a dilemma felt by informants when dealing with the reality of the dark side, because the principle of life is contrary to the culture (dark side) of the organization. But the wave of pressure from the community and the responsibility of its role as head of the family demanded that the informants choose to remain in the reality of the dark side. The situation of informants who remain in the dark side is known as secularism. Keywords: Simalakama Pengelola, Pengelola Keuangan, Sisi Gelap Laporan Keuangan, Sekularisme.